Development and testing of a continuous power operated coconut husker - Anu S Chandran (Department of Farm Power Machinery and Energy, Kelappaji College of Agricultural Engineering and Technology, 2012)
A continuous power operated coconut husking machine for large scale husking of coconuts was developed, tested and its performance evaluated. The major parts are feeding chute, a husking unit, a husk separating unit and power transmission unit. The coconut fed at the feeding chute and in the clearance between the inlet and the drum is slightly compressed and forced to execute rolling or revolutions. In the process, the blade penetrates the husk and punctures it along different planes. The shear force exerted upon the coconut by the blades of the rotating drum and the concave cause to rip open the husk along different planes. The full coconuts with punctured and softened husk fall into the husk separating unit which consists of two knurling rollers. There the softened and punctured husk is separated and the nut emerges at the outlet. The prime mover used is a 3 φ squirrel cage induction motor of 2.2 kW. This rotation is bifurcated to rotate the husking unit and to the separating unit. A speed reduction unit with gear ratio of 30:1 is used to reduce the motor speed from 1440 rpm to 48 rpm. The speed of the motor is also bypassed to the knurling rollers by means of chain drive, by which the speed is reduced from 1440 to 160 rpm through chain and sprockets units. All components are fixed on the frame. The studies show that the minimum and maximum time required for complete husking of a green coconut were 6 s and 22 s and that for a dry coconut was 3 s and 15 s respectively. Thus the mean time required for complete husking of green coconut is 11.6 s and that of dry coconut is 9.5 s. The average capacity of continuous power operated coconut husking machine is much better and found out as 356 nuts per hour compared to the manual method and by husking by commercial model. Also the efficiency, the percentage of nut breaking and the average energy requirement was 82.79 %, 3.83 % and 0.7365 W respectively. The total operating cost of continuous power operated coconut husking machine is Rs. 95.374 per hour and the cost of husking per nut is about Rs. 0.267. Considering its performances, the mechanism developed in this study is promising.